Multiple mechanisms in which agricultural insects respond to environmental stressors: canalization, plasticity and evolution - Gutiérrez, Yeisson (Revista de Ciencias Agrícolas, 2020)
Insects are a paramount component of biodiversity in terms of taxonomic richness, ecological functions and ecosystem services. However, many human activities have negative consequences on such organisms, causing changes in their morphology, physiology, behaviour, and even causing mass deaths leading to the well-recognized insect decline phenomenon. Although the effects of some environmental stressors (e.g. global warming and pesticides) on insect biology are fairly well understood, there is a plethora of stressors that that have only recently been considered. Additionally, although the exposure to multiple stressors is a common scenario in natural conditions, our knowledge on insect responses in this regard is still incipient. Knowledge that is in much need to inform policy makers in the fight against global change. Here, a short review on prominent environmental stressors, and the known responses that insects may exhibit, which are summarized as canalization, plasticity and evolution is provided. Furthermore, an outlook and recommendation for future studies aiming to elucidate the effects of environmental stressors (both lone and mixed) on insect biology is given. This manuscript advocates for controlled (lab or semi-field) manipulative experiments that implement realistic environmental conditions and that ideally combine several stressors.